(untitled) (Nexus International Journal of Science and Education, 2024)
This study investigated the impact of teacher training in Agriculture on the readiness of learners in Technical Vocational Education and Technology Livelihood Education (TVE-TLE) within the Senior High School Track in the Dujali District, Davao del Norte Schools Division. Employing a non-experimental descriptive-correlational research design, data was collected from a randomly selected sample of TVE-TLE teachers using an adapted survey instrument. The analysis included Mean scores, Pearson r, and Simple Linear Regression Analysis to determine correlations between teacher training domains and student readiness. Results revealed that teacher training in Agriculture is moderately extensive, while learners exhibit extensive readiness for TVE-TLE. Significant positive correlations were found between various domains of teacher training—such as knowledge and content mastery, pedagogical skills, hands-on experience, technology integration, and assessment and evaluation—and learners’ readiness. This underscores the importance of comprehensive teacher training programs in Agriculture to enhance student preparedness in vocational education. The study suggests further exploration of the long-term impacts of integrating agricultural and technological education in the senior high school curriculum.